(untitled) (Journal of Management and Educational Sciences, 2025)
This study aims to examine the effect of professional collaboration among teachers on professional alienation. The study was conducted using a relational screening model. According to the results of the study, it is seen that the perceptions of professional collaboration among teachers are above average and the perceptions of work alienation are below average. In the examination by gender; the perceptions of professional collaboration and work alienation of the teachers participating in the study do not change according to women and men. In the examination by marital status; the perceptions of professional collaboration and work alienation of the teachers participating in the study do not change according to whether they are married or single. In the examination by educational status; the perceptions of professional collaboration and work alienation of the teachers participating in the study do not change according to their undergraduate and graduate degrees. In the examination by age groups; the perceptions of professional collaboration and work alienation of the teachers participating in the study do not change according to being in different age groups. In the examination by years of service; the perceptions of professional collaboration and work alienation of the teachers participating in the study do not change according to being in different years of service groups. Finally, no statistically significant relationship was found between the perceptions of professional collaboration among teachers and the perceptions of work alienation. Again, professional collaboration scores among teachers do not significantly predict work alienation total score perceptions.